PRAWO RZYMSKIE W ŚWIECIE WSPóŁCZESNYM WEDŁUG HENRYKA KUPISZEWSKIEGO - Sondel, Janusz (Zeszyty Prawnicze, 2016)
Roman Law In The Contemporary World According To Henryk Kupiszewski Summary The 1988 publication of Henryk Kupiszewski’s book on Roman law and the contemporary world (Prawo rzymskie a współczesność) was a milestone in Polish scholarship. It was written in reaction to the attempts which had been continually undertaken under the People’s Republic of Poland to remove Roman law from the teaching syllabus. The book triggered vociferous protest against the attempt to turn the faculties of law at Polish universities into vocational colleges, at the same time stimulating research on Roman law, not only in its historical aspect but also from the point of view of its value for the present times. An image emerged of Kupiszewski as an outstanding scholar of the humanities, for whom the ethical values in Roman law were just as important as the institutions it created which were subsequently adopted by the legislative systems of latter-day civilised states. Professor Kupiszewski, an advocate of the theory of continuity in the Roman culture and civilisation following the Germanic invasion, drew attention to two factors which turned out to be particularly relevant for the continuation of Roman law – education and the notarial service. He held that especially the latter was of seminal importance, since the formulas notaries reproduced time and again in documents carried the precepts of Roman law well into the Middle Ages. He attributed a special significance to the inspiration Roman law engendered, which he saw as its principal contemporary value. And one can hardly disagree if one recalls a remark he made, that “Justinian’s compilation is a rich store full of things that are required nowadays” is still being confirmed in the work of today’s specialists in civil law.